Peruvian Subduction Surface Model for Seismic Hazard Assessments - Vergaray Astupina, Luis Fernando; Cornejo, Renzo S.; Aguilar B., ZenÃ³n (Salehan Institute of Higher Education, 2019)
Throughout the years seismic hazard calculations in Peru have been developed using area sources models, having to date a great variety of models, however, since they are discretized planar models, they cannot adequately represent the continuity and subduction characteristics of the Nazca Plate. The main objective of this work is the developing of a surface subduction model (SSM), useful for seismic hazard assessments as well as the revision and control of previous models used in this sort of assessments. In this study a spatial interpolation was performed employing the Local Polynomial Interpolation method to capture short-range variation in addition to long-range trends. The data base is based on the compilation of seismic catalogs from Peruvian and international institutions such as the IGP, the USGS, the ISC and others, subsequently, in order to have independent events the elimination of duplicate events, aftershocks and foreshocks was carried out. Then, by interpolation of the focal depths of the independent events, a subduction surface model (SSM) was generated as well as a Standard Error Surface which supports a good correlation of the model. Furthermore, 14 transversal sections of the SSM was employed to compare with the hypocenterâ€™s distributions, evidencing a good correlation with the spatial distribution of the events, in addition to adequately capturing the subduction characteristics of the Nazca Plate. Finally, a comparison was made between 2 Peruvian area models for seismic hazard and SSM developed in the present research, evidencing that seismic source models of the area type have deficiencies mainly in the depths they consider, thus is recommended the use of the present model for future seismic hazard assessments.